Aligning post-merger information systems with corporate strategies. Empirical evidence in a bank merger - Paola Dameri, Renata (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Information System integration is one of the most important challenges in post merger activities. The role of Information System in supporting business processes, products, customer relationships and the daily work of employees in the target company is central. For this reason, the IS rdesign in post-merger activities is both a threat and an opportunity: a threat, because to fail the IS integration could mean the failure of the merger; an opportunity, because to redesign the IS could help to better align it with the new strategic goals of the post-merger company and to gain better performance. However, merged companies generally aims especially at operational goals regarding IS integration, such as cost savings and risk reduction. They overlook the opportunity to align the target IS with M&A strategic aims. In this paper, the author studies the opportunity deriving from a M&A operation, to align IS with corporate strategies; theoretical considerations are supported by empirical evidence in a business case, regarding the most important Italian M&A in the banking sector. The paper suggests a set of business practices and assessment instruments to support management choices in post -merger IS integration and alignment.